2022
DOI: 10.1021/acs.joc.1c02491
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Borane-Catalyzed Reductive Amination of Aniline and Benzaldehyde with Dihydrogen: The Origins of Chemoselectivity

Abstract: Density functional theory calculations are used in this study to investigate the product selectivity and mechanism of borane-catalyzed reductive aldehyde amination by a H2 reducing agent. Knowing that different boranes yield different products, two typical boranes, (B­(2,6-Cl2C6H3)­(p-HC6F4)2 and B­(C6F5)3), are studied. Of the seven possible pathways of B­(2,6-Cl2C6H3)­(p-HC6F4)2-catalyzed aldehyde amination analyzed herein, four are favorable. Three of the four favorable pathways involve imine intermediates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The 3D-optimized structures were visualized using the CYLview program [ 47 ], and the calculated frequency values were used to correct the free energy at 298.15 K and 1 atm. Based on the “the theory of free volume” [ 48 , 49 , 50 , 51 , 52 , 53 ], a correction factor of −2.55 (or 2.55) kcal mol −1 was added to the free energy values to account for the effect of the ideal gas phase model in overestimating the contribution of entropy. Meanwhile, the Gibbs energies were corrected to standard state 1 M [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 3D-optimized structures were visualized using the CYLview program [ 47 ], and the calculated frequency values were used to correct the free energy at 298.15 K and 1 atm. Based on the “the theory of free volume” [ 48 , 49 , 50 , 51 , 52 , 53 ], a correction factor of −2.55 (or 2.55) kcal mol −1 was added to the free energy values to account for the effect of the ideal gas phase model in overestimating the contribution of entropy. Meanwhile, the Gibbs energies were corrected to standard state 1 M [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed using the software Gaussian16. 40 The geometries of all minima and transition states were optimized and characterized at the M06-2X/6-311G** level of theory, [41][42][43][44] and the calculations were conducted in solvent, according to the SMD 45 method. To obtain accurate energy values, single-point energy calculations of the minimum energy conformers were conducted at the M06-2X/def2TZVP level of theory.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, few studies have computationally probed systems that do not contain transition metal catalysts, with even fewer studies analyzing boron complexes. In the study of Zhao et al ., 18 DFT was used to examine the reaction mechanisms of borane-catalyzed reductive amination between benzaldehyde and aniline, with molecular hydrogen as the reducing agent and tetrahydrofuran (THF) as the solvent. Their results showed that the product of this reaction varied depending on the nature of the Lewis acid catalyst (borane complexes) and could in fact be controlled by adjusting the natural charge on the boron atom.…”
Section: Introductionmentioning
confidence: 99%